Representasi Simbolisme Pemulihan Emosional melalui Lirik dan Unsur Musikal Lagu ‘Membasuh’ dalam Konteks Musik Folk Kontemporer - Anisa Azmi Ismail (Institut Seni Indonesia Denpasar, 2026)
Purpose: This study aims to examine the representation of emotional healing symbolism in the song Membasuh by Hindia and Rara Sekar through an analysis of its lyrics and musical elements within the context of contemporary folk music. Method: A qualitative content analysis method was employed to explore the narrative meanings of the lyrics and their relation to musical features such as harmony, tempo, and vocal delivery. Result and Discussion: The findings reveal that the metaphor of “washing” symbolizes inner cleansing, reinforced by a simple arrangement and an intimate musical atmosphere.Implication: Membasuh illustrates emotional recovery through the synergy of narrative and music, while also affirming the role of folk music as a medium for reflection and psychological healing.